SATIRE IN CONTEMPORARY ARABIC FICTION - Bhat, Kaffeel Ahmad; Baba, Rayees Ahmad (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This article explores the complex world of satire in modern Arabic fiction, looking at how authors use humor as a potent social critique weapon. The article examines the wide range of literary genres where satire is used by writers to highlight social concerns, question accepted wisdom, and elicit introspective thinking via a lens that strikes a balance between wit and critique. Utilizing a range of noteworthy pieces, the examination delves into the complex relationship between humor and cultural criticism, demonstrating the adaptability of satire as a rebellious element in Arab literary works. The writers create a satirical fantasy that both entertains and challenges the complexity of the Arab world through crazy storylines and deft wit. The purpose of this investigation is to clarify how satire has changed in recent Arabic fiction.